1986
DOI: 10.1111/j.1365-2125.1986.tb05172.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ and inter‐individual variation in pharmacokinetics of intravenously infused amoxycillin and ampicillin to elderly volunteers.

Abstract: 1 The purpose of this study was to investigate the disposition of two aminopenicillins and their intra-and inter-individual variation in pharmacokinetic parameters in healthy, elderly volunteers. Two groups, each of 12 active, community-dwelling volunteers between 69 and 83 years of age participated. One group was given 500 mg of amoxycillin, the other group 500 mg of ampicillin as single i.v. infusions. Within the drug groups each volunteer was given the infusion at two different occasions separated by a time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…Thus, the absorption of amoxicillin appears too irregular to be generally described by a simple first-order or zero-order process. By contrast, a successful fit of a two-compartment disposition model to the IV data was obtained, confirming the previous report on the stability of the disposition of amoxicillin [19].…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the absorption of amoxicillin appears too irregular to be generally described by a simple first-order or zero-order process. By contrast, a successful fit of a two-compartment disposition model to the IV data was obtained, confirming the previous report on the stability of the disposition of amoxicillin [19].…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, prior knowledge of the structural PK model and the average disposition parameters for the serum concentration profiles and their variability from published studies (4,5,29,30,49,51) were incorporated in the present analyses. As those studies were conducted with young healthy volunteers, the amoxicillin clearance reported by Sjovall et al (53) for elderly subjects was used. This was in agreement with the age-related decrease in renal function predicted by the formula of Cockcroft and Gault (13) on the basis of the CL values from the other studies.…”
Section: Methodsmentioning
confidence: 99%
“…The PK of ampicillin have been studied in children and adults (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), but data on dosing in the neonatal population are sparse. Current dosing regimens take into account the gestational age (GA)-and postmenstrual age (PMA)-related variation in renal drug clearance and recommend lower doses and less frequent dosing in the most premature neonates (1).…”
mentioning
confidence: 99%